2012
DOI: 10.1007/s11418-012-0713-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased effects of ginsenosides on the expression of cholesterol 7α-hydroxylase but not the bile salt export pump are involved in cholesterol metabolism

Abstract: An extract from red ginseng [steamed and dried roots of Panax ginseng C.A. Meyer (RGE)] has been shown to have various actions on physiological functions. The mechanisms by which RGE promotes cholesterol metabolism in the liver are unclear, but RGE decreases the plasma levels of cholesterol. We investigated whether RGE affected the mRNA expression of cholesterol metabolism-related proteins such as cytochrome P450 (CYP)7A1 and bile salt export pump (BSEP) in the liver in hypercholesterolemic rats and rat primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…Of note, the present study further revealed that siRNA depletion of LXRα significantly diminished the protective effect of YXS, while knockdown of PPARα, PPARβ and ERα only slightly blunted the effect of YXS, suggesting that the action of YXS is mainly dependent on LXRα. In line with this finding, expression of cardiac LXRα and its target genes was upregulated the most by YXS, which is consistent with earlier reports that both “sovereign” ingredients in YXS ( Radix Ginseng and Salvia Miltiorrhiza) are potent agonists of LXRs 12 44 . Collectively, our findings provide the first evidence for the association of TCM and NRs in acute ischemic heart injury, and suggest that NRs might be important mediators of the cardio-protective effects of various TCM formulas.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Of note, the present study further revealed that siRNA depletion of LXRα significantly diminished the protective effect of YXS, while knockdown of PPARα, PPARβ and ERα only slightly blunted the effect of YXS, suggesting that the action of YXS is mainly dependent on LXRα. In line with this finding, expression of cardiac LXRα and its target genes was upregulated the most by YXS, which is consistent with earlier reports that both “sovereign” ingredients in YXS ( Radix Ginseng and Salvia Miltiorrhiza) are potent agonists of LXRs 12 44 . Collectively, our findings provide the first evidence for the association of TCM and NRs in acute ischemic heart injury, and suggest that NRs might be important mediators of the cardio-protective effects of various TCM formulas.…”
Section: Discussionsupporting
confidence: 92%
“…In particular, many NRs such as LXRα and ERs and are pivotal modulators of redox balance and myocyte survival in reperfused hearts 7 26 27 . Interestingly, previous studies on non-myocyte (e.g., HepG2 and HeLa) cells reported that almost all the individual components of YXS have agonistic activities on one or more of the following NRs: LXRs, PPARs, ERs, progesterone receptor (PR) and pregnane X receptor (PXR) ( Supplementary Table S1 ) 12 44 45 46 47 48 . However, in the present study, only LXRα, PPARα, PPARβ and ERα, but not PR or PXR, were upregulated by YXS in ischemic/reperfused myocardium, which might be explained by the tissue-specific distribution of NRs in mammals: PR is barely detectable in the heart 49 and PXR is much less abundantly expressed in the myocardium than in other tissues 50 .…”
Section: Discussionmentioning
confidence: 99%
“…Total RNA was extracted from murine small intestines and HepG2 cells using TRIzol. mRNA expression was measured using RT-PCR, as described previously (20,21). The oligonucleotide sequences for each mRNA target are shown in Table 1.…”
Section: Determination Of Mrna Levels By Real-time Reverse Transcriptmentioning
confidence: 99%
“…Total RNA was extracted from mouse primary hepatocytes, PANC1 cells and HepG2 cells using Sepasol RNA I Super G. The mRNA expression was measured using RT-PCR, as described previously (30,31). The oligonucleotide sequences for each mRNA target were as follows: mouse PIP5K1A…”
Section: Real-time Reverse Transcription Polymerase Chain Reaction (Rmentioning
confidence: 99%